Lactobacillus plantarum IS-10506 probiotic administration increases amlodipine absorption in a rabbit model - Saputri, Febrina A. (J Int Med Res, 2018)
OBJECTIVE: Probiotics are beneficial in human health. In this study, we investigated the effect of probiotics on absorption of amlodipine, a dihydropyridine calcium antagonist used in the treatment of angina and hypertension, in a rabbit model. METHODS: Lactobacillus plantarum IS-10506 probiotic was administered for 14 days to male New Zealand rabbits. Blood samples were collected before and after probiotic supplementation. Amlodipine (10 mg) was then administered to all groups. Blood samples from a marginal vein were withdrawn at 5, 15, 30, 60, and 120 minutes to determine amlodipine concentrations in rabbit plasma. RESULTS: Amlodipine concentrations in the L. plantarum IS-10506 group were 4.95 ± 1.22, 8.71 ± 0.69, and 12.48 ± 2.53 ng/ml, and those in the control group were 1.69 ± 0.31, 3.89 ± 1.23, and 7.17 ± 1.85 ng/ml at 30, 60, and 120 minutes, respectively after administration of amlodipine. Amlodipine concentrations in the L. plantarum IS-10506 group were significantly higher than those in the control group at 30, 60, and 120 minutes after amlodipine administration. CONCLUSION: Our results suggested that supplementation of L. plantarum IS-10506 significantly increases amlodipine plasma concentrations in rabbits.